Acoela (Acoelomorpha) from Bocas del Toro, Panama - Hooge, Matthew D.; Tyler, Seth (Zootaxa, 2008)
Twenty species of Acoela, nine new to science, are reported from Bocas del Toro, on the Caribbean coast of Panama. The species include two from the family Childiidae (Childia crassum, Childia groenlandica), two from Convolutidae (Con- voluta sp., cf. Heterochaerus sargassi), one from Dakuidae (Daku riegeri sp. nov.), six from Haploposthiidae (Exocelis reedi sp. nov., Haploposthia vandula, Kuma albiventer, Kuma blacki sp. nov., Pseudohaplogonaria caribbea, Unnamed Species 1), one from Hofsteniidae (Hofstenia miamia), seven from Isodiametridae (Aphanostoma collinae sp. nov., cf. Avagina marci, Diatomovora jacki sp. nov., Isodiametra cuernos sp. nov., Isodiametra nicki sp. nov., Praeaphanostoma foramivora sp. nov., Praeconvoluta bocasensis sp. nov.), and one from Sagittiferidae (Antrosagittifera corallina). The genus Exocelis is transferred from the defunct family Otocelididae to the family Haploposthiidae.